Model Lanskap Permukiman Tradisional Masyarakat Gayo, Kabupaten Aceh Tengah, Provinsi Aceh - Rizky, Annisa Fathiya; Gunawan, Andi; Manningtyas, Rosyi Damayanti Twinsari (Jurnal Lanskap Indonesia, 2025)
Traditional settlements play a crucial role in shaping and preserving the unique identities of communities functioning as a repository of cultural heritage and historical significance, thus contributing greatly to the collective identity of a population. Such settlements are prevalent in Indonesia, including the Gayo indigenous community. This study aims to identify and analyze landscape characters and models of traditional Gayo settlements. The research was conducted in Toweren Uken, Central Aceh Regency, Aceh Province. This research was conducted using a qualitative descriptive method, with research stages including tracing customary scripts, interviewing cultural figures, and field observation. Content analysis is conducted on literature related to the elements that shape settlement landscapes, while spatial analysis carried out after field observations are completed. The landscape characteristics of traditional Gayo settlements show hilly terrain with land cover dominated by agricultural fields, with settlements located surrounded by agricultural fields and hills. Natural elements identified within the town include Lake Lut Tawar, mountains, hills, and rivers. Man-made elements include rice fields, mixed gardens, and residential areas. The settlement area itself contains both traditional and modern houses, a mosque, and cemeteries. These elements consist of traditional houses, mersah, joyah, keben, beranang, and open areas used for agriculture and vegetable farming. The landscape model of Gayo traditional settlements forms a cluster pattern, with the settlements surrounded by rice fields.